Effect of Long-Wavelength Track Irregularities on Vehicle Dynamic Responses - Tao Xin; Pengsong Wang; Yu Ding (Shock and Vibration)
Long-wavelength track irregularities have obvious influence on ride comfort and running stability of high-speed trains. Meanwhile, it brings risk to the inspection of track irregularities since ordinary inspection equipment has difficulties in covering long wavelengths. Previous research on the effect of long-wavelength track irregularities is rare. In order to find the relationship between long-wavelength irregularities and vehicle dynamic responses, a numerical vehicle-track coupling dynamic model based on multibody dynamics and finite element theories is established by using a self-compiling program. One case study is given as an example to show the methodology of determining the sensitive long wavelength and management amplitude of track longitudinal-level irregularities in high-speed railway. The simulation results show that the sensitive long wavelength has a strong correlation with train speed and natural frequency. The simulation and field test results are in good agreement.